NUCLEAR MOMENTUM DISTRIBUTION WITH FRACTIONAL OCCUPATION PROBABILITIES OF THE SURFACE ORBITS - Kosmas, T. S.; Vergados, J. D. (HNPS Advances in Nuclear Physics, 2020)
Simplified expressions for calculating nucléon momentum distributions are derived in the context of the harmonic oscillator shell model and in its modification in which fractional occupation probabilities of the surface orbits are used. The method is applied to study the proton momentum distribution of the spherical nucleus 40Ca. The values of the partial occupation probabilities used had been previously determined by fitting to the experimental elastic form factor data.